Pengaruh Model Pembelajaran Inquiri dan Gaya Belajar Terhadap Hasil Belajar Geografi Materi Mitigasi Bencana Alam Siswa Kelas XI SMAN 11 Kendari - Asrin; Sitti Kasmiati; La Ode Nursalam; Andrias (Jurnal Penelitian Pendidikan Geografi, 2024)
Senior High School 11 Kendari is one of the schools in Wua Wua District, Kendari City that has low Geography learning outcomes. The ineffective learning model makes students' interest in learning decrease. This study aims to: 1) determine the description of Geography learning outcomes based on learning styles; 2) determine the effect of Inquiry learning models and learning styles on Geography learning outcomes on Natural Disaster Mitigation material for grade XI IPS students of SMA Negeri 11 Kendari. The type of research used is experimental research. The population of the study was 73 students, with a research sample of 27 students. The research data in the form of quantitative data was obtained from tests and questionnaires. The results of the study showed: 1) the average value of learning outcomes were pre-test 41.19 and post-test 86.67; and the average value of learning outcomes based on students' learning styles, kinesthetic pre-test 35.13, visual pre-test 50.27, and auditory pre-test 34.75; and kinesthetic post-test 86.88; visual post-test 89.45; and auditory post-test 82.25; 2) the results of hypothesis testing using one way ANOVA with probability value Sig. = 0.00>0.05 then ho is rejected and ha is accepted. Thus there is an influence of Inquiry learning model and learning style on Geography learning outcomes